HGG-06. USE OF TUMOR TREATING FIELDS DELIVERED WITH CONCURRENT TEMOZOLOMIDE AND LOMUSTINE AS ADJUVANT THERAPY IN A PATIENT WITH PEDIATRIC GLIOBLASTOMA. Issue 2 (22nd June 2018) - Supples, Sarah; Couture, Daniel; Whitlow, Christopher; Pearsall, Katharine; Chan, Michael; Kram, David
Abstract: BACKGROUND: Pediatric glioblastoma (GBM; WHO grade IV astrocytoma) continues to carry a poor prognosis. While the use of concurrent and adjuvant temozolomide (TMZ) has been adopted as a standard treatment in adults, there is no standard systemic therapy for pediatric GBM. Recent studies in adults suggest benefit to the addition of tumor treating fields (TTF) to standard TMZ-based chemoradiotherapy, while a recent study in children showed improvement with the addition of lomustine (CCNU) to standard TMZ-based chemoradiotherapy. No studies to this point have been published using the combination of TMZ, TTF, and CCNU in either adult or pediatric GBM. METHODS: A single patient was treated with aggressive local surgery achieving gross total resection. This was followed by 60 Gy in 30 fractions with concurrent temozolomide (75 mg/m2) given daily during radiotherapy. Post-radiation adjuvant therapy consisted of dose escalated temozolomide (160 mg/m2) given on days 1-5 of a 42-day cycle, CCNU (90 mg/m2) on day 1, and continuous tumor treating fields (started with cycle 1 of adjuvant chemotherapy). RESULTS: Chemoradiotherapy was tolerated well without grade III or IV toxicity. Thus far, the patient has received 2 cycles of adjuvant temozolomide/CCNU without grade III or IV toxicity. At 3 months post-radiotherapy, there is no evidence of tumor recurrence. CONCLUSION: We report the first case of a pediatric patient with GBM receiving a maintenance combination of TTF, TMZ, and CCNU after tumor resection and standard TMZ-based chemoradiotherapy. Prospective trials are necessary to validate the tolerability, safety, and efficacy of this aggressive combination therapy.